Halal Identification for Meatballs in Pasar Tambun, Bekasi, West Java By Acrylamide Gels - Hidayati, Wahyu; Apriaji, Meta; Situmorang, Almawati; Agustian, Ifany; Janah, Miftahul (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2019)
Halal foods are important for Moslems and there is a Moslem’s duty to eat only Halal foods which is stated in Holly Qur’an. Moreover, government already made some regulations related to Halal certification which should be obeyed by food industries, including home industries. This research aimed to detect a porcine component in meatballs sold in Pasar Tradisional Tambun, Bekasi, West Java by using SDS-PAGE Here, we combined mechanical and chemistry methods to extract the proteins and compared the protein profiles on an acrylamide gel. We got specific bands of bovine and porcine proteins according to proteins bands that showed on the gel and after comparing with the samples we found that one sample had combining profiles in the extract. We concluded that three samples used in this research were halal, meanwhile, another sample containing porcine substances. Keywords: Halal, Proteins, Bovine, Porcine, Meatballs, SDS-PAGE.